1997
DOI: 10.1159/000177996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tea Decoction Given to Rats ad libitum for a Relatively Long Time on Body Weight Gains and Iron, Copper, Zinc, Magnesium Concentrations in Blood, Liver, Duodenum and Spleen

Abstract: The aim of our study was to examine the influence of tea decoction given ad libitum for 15 days on body weight gains and on nonheme iron, copper, zinc and magnesium concentrations in the blood from a semisynthetic diet provided to healthy rats. We have also evaluated the reserves of these essential minerals in the liver, duodenum and spleen. Our findings indicate that the tea decoction significantly reduced the total body weight growth in the tea group as compared to the control group (p < 0.0001). The total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
13
2
Order By: Relevance
“…The enhancing effect of green tea decoction on zinc status was consistent with that found in our previous study: we have shown that a single dose of black tea decoction (6%) given to rats for 2 weeks decreased iron status. In contrast, it significantly increased zinc in the total blood by nearly 30%, without affecting the zinc concentration in organs [7]. Our results on zinc status were more pronounced than those of Zeyuan et al [25] who reported that the amounts of black or green tea leaves (0.6, 1.2 and 2.4%) introduced in the diet of rats or in the form of a drinking water extract significantly reduced the iron and calcium status.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The enhancing effect of green tea decoction on zinc status was consistent with that found in our previous study: we have shown that a single dose of black tea decoction (6%) given to rats for 2 weeks decreased iron status. In contrast, it significantly increased zinc in the total blood by nearly 30%, without affecting the zinc concentration in organs [7]. Our results on zinc status were more pronounced than those of Zeyuan et al [25] who reported that the amounts of black or green tea leaves (0.6, 1.2 and 2.4%) introduced in the diet of rats or in the form of a drinking water extract significantly reduced the iron and calcium status.…”
Section: Discussioncontrasting
confidence: 80%
“…Moreover, it has been demonstrated that the iron status was low in people who regularly consumed tea [5,6]. In our precedent study [7], we have observed that a single dose of black tea decoction given ad libitum to rats for a middle period of time (2 weeks) significantly reduced the iron concentration in the total blood, liver and duodenum. In contrast, it significantly increased zinc, copper and magnesium concentrations in the total blood.…”
Section: Introductionmentioning
confidence: 53%
“…Hamdaoui et al (1997) found that tea decoction significantly increased zinc, copper and magnesium concentrations in the total blood of healthy rats. Also, Etcheverry et al (2012) found that polyphenols did not interfere with the zinc absorption while studying the in vitro bioaccessibility and bioavailability methods for different bioactive compounds.…”
Section: Introductionmentioning
confidence: 95%
“…The formation of complexes with copper may just have opposite effects. Interestingly, tea caused an increase in copper absorption when tested in rats [29][30][31]. These opposite effects are likely explained by the weaker affinity of polyphenols for copper as compared to iron.…”
Section: Chelation Of Metal Ionsmentioning
confidence: 99%